(untitled) ("Conference on Universal Science Research 2023", 2023)
This comprehensive article delves into the multifaceted issue of interference across various domains, including technology, communication, and mental processes. It discusses the disruptive nature of interference, its sources, and provides valuable strategies for both preventing and overcoming it. The article emphasizes proactive measures such as identifying sources, implementing shielding, and establishing clear communication channels to prevent interference. Additionally, it highlights the significance of adaptability, collaboration, education, and mindfulness in overcoming interference, offering practical insights for individuals and organizations seeking effective solutions. Overall, this annotation encapsulates a holistic approach to understand, prevent, and mitigate the challenges posed by interference in different spheres of life.